2004
DOI: 10.1007/10.1007/s10616-004-5123-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of exogenous hTERT to immortalize primary human cells

Abstract: A major obstacle to the immortalization of primary human cells and the establishment of human cell lines is telomere-controlled senescence. Telomere-controlled senescence is caused by the shortening of telomeres that occurs each time somatic human cells divide. The enzyme telomerase can prevent the erosion of telomeres and block the onset of telomere-controlled senescence, but its expression is restricted to the early stages of embryonic development, and in the adult, to rare cells of the blood, skin and diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 41 publications
2
70
0
1
Order By: Relevance
“…This may contribute to the activation of hTERT transcription by E6 in early passage human keratinocytes. hTERT expression plays an important role in the immortalization of human cells by preventing the shortening of telomeres and blocking the onset of telomere-controlled senescence (Lee et al 2004 ).…”
Section: 6mentioning
confidence: 99%
“…This may contribute to the activation of hTERT transcription by E6 in early passage human keratinocytes. hTERT expression plays an important role in the immortalization of human cells by preventing the shortening of telomeres and blocking the onset of telomere-controlled senescence (Lee et al 2004 ).…”
Section: 6mentioning
confidence: 99%
“…Another investigation [25] has outlined that exogenously stably transfected hTERT used to prevent telomere shorterning in fact can immortalize primary human cells without showing cancerous phenotypic properties. In another example, immortalization of pleomorphic adenoma has been obtained via stable hTERT transfection [26].…”
Section: The Immortality Principlementioning
confidence: 99%
“…In the above section 'the immortality principle' I outline the situation whereby cells may be immortalized without necessarily causing their malignant transformation -even cells whose origin is that of a benign neoplasm [24][25][26].…”
Section: Presently Proposed Genetic Ex Vivo Modification Of Differentmentioning
confidence: 99%
“…In addition, mouse (m)TERT levels also appear to diminish over time in primary cell cultures, in part, leading to cell senescence and cell death (1,6,10,14,18). Work with human primary cell lines has shown that ectopic expression of human TERT (hTERT) can lead to continued cell replication and hence, immortalization (21,31,37,39). More importantly, recent reports have shown immortalized hTERT cells remain differentiated, thus preserving the phenotypic properties that closely resemble in vivo characteristics (37,39).…”
Section: Epithelial; Polycysticmentioning
confidence: 99%